How to manage multiple fibroids in reproductive laparoscopic surgery - Wachyu Hadisaputra; Arie Aldila Pratama (Wolters Kluwer Medknow Publications, 2013)
The incidence of fibroids ranges from 30% to 70% in women of reproductive age, with the peak incidence occurring between 35 and 49 years of age. Risk factors for fibroids include nulliparity, obesity, black ethnicity, family history, polycystic ovarian syndrome, diabetes, and hypertension. Fibroids are present in 5-10% of the patients presenting with infertility. Laparoscopic myomectomy is preferred over abdominal myomectomy because several small incisions are used rather than one larger incision. Related to the small incisions, recuperation is usually associated with minimal discomfort. Women with infertility and fibroids become pregnant after myomectomy in approximately 50% of cases. The pregnancy rate in patients undergoing hysteroscopic and laparoscopic/abdominal myomectomy is 45-49%. Laparoscopic myomectomy is a technically challenging procedure with surgeon-specific limitations. Preoperative treatments with gonadotropin-releasing hormone have been shown to reduce blood loss and shorten operative time. The consensus states that the maximal size must be 8-10 cm and the total number of fibroids should not exceed four. It is important not to perform laparoscopic myomectomies with more than 5-7 large fibroids because in these cases, the procedure is excessively time-consuming and gives the surgeon opportunities to miss the smaller fibroids after the uterus has been incised and repaired in too many places. The role of vasoconstrictors such as vasopressin, epinephrine, and ornipressin help with the control of bleeding from the incised sites. Temporary clipping of the uterine artery is an effective procedure in reducing hemoglobin loss during laparoscopic myomectomy.